The core of an onion : peeling the rarest common food--featuring more than 100 historical recipes - Kurlansky, Mark (Bloomsbury Publishing, 2023)
As Julia Child once said, "It is hard to imagine a civilization without onions." Historically, she's been right-and not just in the kitchen. Uniquely flourishing in just about every climate and culture around the world, onions have provided the essential basis not only for sautés, stews, and stir fries, but for medicines, metaphors, and folklore. Abundantly commonplace yet extraordinarily indispensable, the onion is Kurlansky's newest global food fixation as he sets out to explore how and why the crop reigns over Wales to Italy and everywhere in between. Featuring historical images and his own pen-and-ink drawings, Kurlansky begins with the science behind the only sulfuric acid-spewing plant, then digs through the twenty varieties of onion and the cultures built around them. Among the first domesticated and cultivated crops, onions were seen by the ancient Egyptians as a symbol of eternity, the Greeks as an agent of strength, and the Chinese as a supplement for intelligence. Entering the kitchen, Kurlansky celebrates the raw, roasted, creamed, marinated, and pickled. Including twenty-five recipes from around the world, The Core of an Onion shares the secrets to celebrated Parisian chef Alain Senderens's onion soup eaten to cure late-night drunkenness; Hemingway's raw onion and peanut butter sandwich; and the Gibson, a debonair gin martini garnished with a pickled onion. Just as the smell of sautéed onions will lure anyone to the kitchen, The Core of an Onion is sure to draw readers into their savory stories at first taste.